2014
DOI: 10.1063/1.4862056
|View full text |Cite
|
Sign up to set email alerts
|

Electron ionization of open/closed chain isocarbonic molecules relevant in plasma processing: Theoretical cross sections

Abstract: In this paper, we report theoretical electron impact ionization cross sections from threshold to 2000 eV for isocarbonic open chain molecules C4H6, C4H8, C4F6 including their isomers, and closed chain molecules c-C4H8 and c-C4F8. Theoretical formalism employed presently, viz., Complex Scattering Potential-ionization contribution method has been used successfully for a variety of polyatomic molecules. The present ionization calculations are very important since results available for the studied targets are eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Targets with a higher IP and closed chains show a smaller Q ion than those with open chains and lower IP values. Lopes et al, 20 and R. Patel et al 38 also reported these observations. For example, 1-pentyne and 1-butyne have the maximum ionization potential of 10.100 and 10.180 eV, respectively, with one C−C triple bond, and these targets show the best satisfactory results if we compare them to the experimental and theoretical results of Szmytkowski et al 15,17 Similarly, bicyclo[1.1.1]pentane is a closed chain isomer with an IP of 9.650 eV, showing a smaller cross-section magnitude and better results than all other targets.…”
Section: ■ Results and Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Targets with a higher IP and closed chains show a smaller Q ion than those with open chains and lower IP values. Lopes et al, 20 and R. Patel et al 38 also reported these observations. For example, 1-pentyne and 1-butyne have the maximum ionization potential of 10.100 and 10.180 eV, respectively, with one C−C triple bond, and these targets show the best satisfactory results if we compare them to the experimental and theoretical results of Szmytkowski et al 15,17 Similarly, bicyclo[1.1.1]pentane is a closed chain isomer with an IP of 9.650 eV, showing a smaller cross-section magnitude and better results than all other targets.…”
Section: ■ Results and Discussionmentioning
confidence: 76%
“…Targets with a higher IP and closed chains show a smaller Q ion than those with open chains and lower IP values. Lopes et al, 20 and R. Patel et al 38 also reported these observations. For example, 1-pentyne and 1-butyne have the maximum ionization potential of 10.100 and 10.180 eV, respectively, with one C−C triple bond, and these targets show the best satisfactory results if we compare them to the experimental and theoretical results of Szmytkowski et al 15,17 Similarly, bicyclo[1.1.1]pentane is a closed chain isomer with an IP of 9.650 eV, showing a smaller cross-section magnitude and better results than all other However, there are significant contradictions, such as the fact that the closed chain isomer bicyclo[2.1.0]pentane and the open chain isomer ethenylcyclopropane have the same ionization potential of 8.700 eV, respectively, and that being the closed chain isomer, the cross section magnitude of bicyclo [2.1.0] pentane is higher than that of ethenylcyclopropane.…”
Section: ■ Results and Discussionmentioning
confidence: 76%
“…In figure 2, we have plotted the present ionization results calculated with orbital parameters obtained from RHF and DFT (ωB97X-D/ωB97X) functional for 1,3-C 4 F 6 , 2-C 4 F 6 and c-C 4 F 6 along with the experimental result of Bart et al [30] and the recent theoretical results of Bull et al [31] and Patel et al [37] shows good agreement with the recent BEB computations of Bull et al [31] at low energies and underestimates their data at the peak for 2-C 4 F 6 . Such a comparison is also seen in our previous work [29] where the present DFT (ωB97X) showed excellent agreement with the BEB data of Bull et al [31] for C 2 F 6 , C 3 F 6 and C 3 F 8 .…”
Section: Resultsmentioning
confidence: 99%
“…Jiao et al [36] have also measured the partial and total Q ion of 2-C 4 F 8 . The SCOP and complex CSP-ic method have been successfully employed by Patel et al [37] to compute Q ion for 2-C 4 F 6 , 1,3-C 4 F 6 and c-C 4 F 8 . The Q ion of Patel et al is in good agreement with the experiment of Bart et al [30] for C 4 F 6 isomers at low incident energies, which sharply falls down after the peak and their results for c-C 4 F 8 show good agreement with the experiment of Toyodo et al [32].…”
Section: Although Various C 4 F +mentioning
confidence: 99%
“…Many scholars have carried out experimental and theoretical research on c-C 4 F 8 and its gas mixture. It was found that the insulation performance of c-C 4 F 8 /N 2 , c-C 4 F 8 /CO 2 and c-C 4 F 8 /CF 4 gas mixture is great, indicating that c-C 4 F 8 gas mixture has immense potential for use in MV equipment [12][13][14].…”
Section: Introductionmentioning
confidence: 99%